PENGEMBANGAN LIFE SKILL DALAM PEMBELAJARAN SAINS - Mujakir Mujakir (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
The aim of the article is to develop the science instruction which is oriented in the life skills. The main issues discussed in this writing are life skills, the aim and benefits of the life skills, the school as a better place of instruction, the integration of the the courses, life skills, and the real life, the development of life skills method in science instruction, the suitable method of science instruction for the development of life skills. This article uses documentation approach based on the field phenomenon. Its implication is hoped to increase reader’s view upon the urgent of being professional in education with the life skills competency.